DEVELOPPING INTERACTIVE LEARNING MEDIA USING OBS TO CREATE VIDEO LECTURER FOR "PREACHING ISLAMIC HOSPITALITY" - Ahmad Qorib (Al Ulya: Jurnal Pendidikan Islam, 2021)
Online learning faces a different set of obstacles than classroom-based learning. So that, it’s increases the using of video streaming and lecturer as media for teaching and learning activities. The use of this media in learning al Quran Hadith is intended to attract student's interest in designing blended learning model which combine both classroom-based learning and online learning systems. This media is important in considering that the materials of al Quran Hadith emphasizes more on memory. So that, playing videos repeatedly can help students to remember the materials. The type of this study is a research and development (R & D) which focuses on the developping interactive learning media using OBS studio application to create video lecturer on the material of “preaching Islamic hospitality. The model used in this study is the Borg and Gall's model which is simplified into eight steps, they are: 1). Preliminary research, 2). Planning, 3). Initial product development, 4). Initial product trial / limited trial, 5). Preliminary product enhancement, 6). Larger field trial, 7). Final product test. The products produced from this research are in the form of video lecturer that has been validated by some experts, they are: material experts, media experts and students’s responses as user. Based on the assessment and response, it was concluded that the interactive learning media using OBS studio application to create video lecturer was regarded feasible to be used and developed.